A kind of high-adhesion aluminum foil foam and its processing technology

By using composite polyols, epoxy modified isocyanate, tackification modified chain extender and modified conductive filler, the problems of low bonding performance and electrostatic interference of aluminum foil foam are solved, and high adhesion and good anti-static properties are achieved.

CN118909557BActive Publication Date: 2025-03-25苏州普诺兹电子有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410952487.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-16
Publication Date
2025-03-25
Estimated Expiration
2044-07-16

AI Technical Summary

Technical Problem

The existing aluminum foil foam has low bonding performance and is susceptible to electrostatic interference, which affects the service life of electronic products.

Method used

Composite polyols, epoxy modified isocyanate, tackification modified chain extender and modified conductive filler are used to form high-adhesive aluminum foil foam through specific processes.

Benefits of technology

It significantly improves the bonding and antistatic properties of aluminum foil foam, and reduces the impact of external interference on electronic products.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to a kind of high-adhesion aluminum foil foam and its processing technology, the high-adhesion aluminum foil foam includes release paper I, high-adhesion foam I, aluminum foil, high-adhesion foam II and release paper II arranged in sequence, and the high-adhesion foam includes the following components by mass fraction: 25-35 parts of complex polyols, 15-25 parts of epoxy-modified isocyanates, 4-6 parts of tackifying modified chain extenders, 12-16 parts of modified conductive fillers, 0.05-0.15 parts of dibutyltin dilaurate, 1.5-2.5 parts of foaming agents, and 0.2-0.6 parts of catalysts. The processing technology includes the steps of preparing a foaming mixture, uniformly applying the foaming mixture to the two surfaces of the aluminum foil, covering the release paper to obtain a preliminary product, and obtaining a high-adhesion aluminum foil foam after the preliminary product is matured. The present application has the effect of improving the adhesion performance, antistatic performance and shielding performance of aluminum foil foam, can effectively fix components, reduce the interference effect of static electricity, and shield the influence of electromagnetic waves on product signals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of foam technology, and in particular to a high-adhesion aluminum foil foam and a processing technology thereof. Background Art

[0002] Foam refers to the material obtained by foaming plastic particles. Due to the wide variety of foams and their good elasticity, small weight and fast pressure-sensitive fixation, they are widely used in electronic products and military fields.

[0003] With the development of science and technology, the size of electronic products such as televisions is getting smaller and thinner, and people are also demanding higher and higher service life of these products. Therefore, there are higher requirements for the bonding strength of various components in electronic products. The bonding performance of conventional aluminum foil foam is average and is easily affected by static electricity, which may even cause product damage in severe cases, so it needs to be improved. Summary of the invention

[0004] In order to improve the adhesion and antistatic properties of aluminum foil foam, the present application provides a high-adhesion aluminum foil foam and a processing technology thereof.

[0005] The present application provides a high-adhesion aluminum foil foam and its processing technology using the following technical solutions:

[0006] In the first aspect, the present application provides a high-adhesion aluminum foil foam, which adopts the following technical solution:

[0007] A high-adhesive aluminum foil foam, the high-adhesive aluminum foil foam comprising release paper I, high-adhesive foam I, aluminum foil, high-adhesive foam II and release paper II arranged in sequence, the high-adhesive foam comprising the following components in parts by mass:

[0008] 25-35 parts of compound polyol

[0009] Epoxy modified isocyanate 15-25 parts

[0010] 4-6 parts of viscosity-enhancing modified chain extender

[0011] Modified conductive filler 12-16 parts

[0012] Dibutyltin dilaurate 0.05-0.15 parts

[0013] Foaming agent 1.5-2.5 parts

[0014] Catalyst 0.2-0.6 parts.

[0015] The complex polyol has abundant active groups, good reactivity, and forms a variety of chemical bonds in the foam, thereby improving the adhesion performance of the aluminum foil foam; the epoxy-modified isocyanate introduces epoxy groups into the isocyanate, and the epoxy groups have good reactivity and can form bonds with the surfaces of various substrates, thereby improving the adhesion performance of the aluminum foil foam; the tackifier modified chain extender introduces high adhesion groups through chain extension modification, thereby improving the adhesion performance of the aluminum foil foam; the modified conductive filler has good system compatibility, can reinforce the molecular defects in the foam, and construct a conductive network, thereby improving the antistatic performance; the modified conductive filler can also absorb and scatter electromagnetic waves, dissipate the energy of electromagnetic waves, so that the foam can work synergistically with the aluminum foil, improve the shielding performance, and reduce the impact of external interference on electronic products.

[0016] Preferably, the complex polyols include polyether polyols, polyester polyols and bio-based polyols.

[0017] Polyether polyols, polyester polyols and bio-based polyols have active ester bonds, uniquely arranged carbon and oxygen atoms, etc., which can react with epoxy-modified isocyanates and form hydrogen bonds, van der Waals forces and chemical bonds between molecules, thereby increasing the adhesion properties of aluminum foil foam and its bonding strength with various substrates.

[0018] Preferably, the raw materials for preparing the epoxy-modified isocyanate include 1,4-butanediol diglycidyl ether, triethanolamine and diphenylmethane diisocyanate.

[0019] 1,4-Butanediol diglycidyl ether reacts with triethanolamine to obtain an intermediate product with active hydroxyl groups, and the active hydroxyl groups successfully introduce epoxy groups into isocyanate by reacting with isocyanate groups; the epoxy groups have good surface activity and can promote the bonding of aluminum foil foam with the surface of the substrate. At the same time, the epoxy groups can react with other groups in the system to increase the cross-linking structure in the foam and enhance the stability of the three-dimensional network, thereby enhancing its adhesion.

[0020] Preferably, the mass ratio of 1,4-butanediol diglycidyl ether, triethanolamine and diphenylmethane diisocyanate is 1:0.75:(11.2-13.6).

[0021] The epoxy-modified isocyanate prepared according to the above mass ratio has good activity and can improve the adhesion and stability of the aluminum foil foam.

[0022] Preferably, the raw materials for preparing the tackifying modified chain extender include polymerized rosin, oxalyl chloride and long-chain diol.

[0023] Polymerized rosin has good adhesion properties. The reactivity of polymerized rosin is improved by reacting oxalyl chloride with polymerized rosin, so that long-chain diols are successfully grafted onto the surface of polymerized rosin, and polymerized rosin is introduced into polymer molecules through chain extension reaction, thereby improving the adhesion and stability of aluminum foil foam; polymerized rosin has dielectric properties and wave absorbing properties, which can assist in improving antistatic and shielding properties; long-chain diols have a long carbon chain structure, which can promote intermolecular cross-linking, form more hydrogen bonds and van der Waals forces, improve the durability and stability of aluminum foil foam, and optimize the pore structure of the foam, so that the aluminum foil foam can increase the absorption and reflection of electromagnetic waves through a uniform and delicate pore structure, thereby improving the shielding performance.

[0024] Preferably, the raw materials for preparing the modified conductive filler include a composite filler and a modifier, the composite filler includes conductive carbon black, carbon nanotubes and graphene oxide, and the raw materials for preparing the modifier include boron-containing silane and long-chain diamine.

[0025] There are a large number of electrons distributed on the carbon atom orbits in conductive carbon black, carbon nanotubes and graphene oxide, forming a conjugated π electron system, so they have good conductivity and can effectively absorb electromagnetic waves. Through the oscillation of their own free electrons, they convert the energy of electromagnetic waves into heat energy, promote the attenuation and absorption of electromagnetic waves, and thus improve the antistatic and shielding properties; the aluminum foil foam is modified by boron silane and long-chain diamine to increase the active groups on the surface of the composite filler, thereby improving its system compatibility and reactivity, so that the modified conductive filler can better exert its antistatic and shielding properties.

[0026] Preferably, the raw materials for preparing the boron-containing silane include boric acid and dichlorodicyclopentylsilane.

[0027] By reacting boric acid with dichlorodicyclopentylsilane, the boron element is introduced into silane, which can increase the adsorption effect between the aluminum foil foam and the substrate and enhance the bonding strength between the foam and the substrate. The boron element can also enhance thermal stability and durability, allowing the foam to maintain long-term high adhesion.

[0028] Preferably, the mass ratio of the boric acid, dichlorodicyclopentylsilane and long-chain diamine is (0.22-0.3):1:0.6.

[0029] The modified conductive filler prepared according to the above mass ratio has good system compatibility, antistatic property and shielding property.

[0030] Preferably, the blowing agent includes 4,4'-oxybisbenzenesulfonylhydrazide, and the catalyst includes N-methylmorpholine and triethylenediamine.

[0031] 4,4'-Bis(benzenesulfonyl)hydrazide has good foaming properties and can make the aluminum foil foam have a uniform and delicate pore structure; N-methylmorpholine and triethylenediamine have high catalytic activity and can promote the foaming process of the foam; the foaming agent and the catalyst work synergistically to optimize the pore structure of the aluminum foil foam, thereby improving the adhesion, antistatic and shielding properties of the aluminum foil foam.

[0032] In a second aspect, the present application provides a processing technology for high-adhesion aluminum foil foam, which adopts the following technical solution:

[0033] A processing technology for high-adhesion aluminum foil foam includes the following steps:

[0034] The composite polyol is heated and decompressed to dehydrate to obtain an anhydrous composite polyol, which is dried and stored for later use; under the protection of a neutral gas, the anhydrous composite polyol is added to an epoxy-modified isocyanate to obtain a prepolymer mixture, a tackifier-modified chain extender, a modified conductive filler and dibutyltin dilaurate are mixed and added to the prepolymer mixture, heated and stirred to react to obtain a prepolymer, a blowing agent and a catalyst are dispersed in the prepolymer, stirred to obtain a foaming mixture, the foaming mixture is uniformly coated on the surface of an aluminum foil to obtain a high-adhesion foam I, a release paper I is covered on the high-adhesion foam I, the surface is turned over, and the foaming mixture is uniformly coated on the other side of the aluminum foil to obtain a high-adhesion foam II, a release paper II is covered on the high-adhesion foam II to obtain a preliminary product, and the preliminary product is matured to obtain a high-adhesion aluminum foil foam.

[0035] The aluminum foil foam prepared according to the above steps has high adhesion, good antistatic property and shielding property.

[0036] In summary, the present application includes at least one of the following beneficial technical effects:

[0037] 1. The complex polyol has abundant active groups, good reactivity, and forms a variety of chemical bonds in the foam, thereby improving the adhesion performance of the aluminum foil foam; the epoxy-modified isocyanate introduces epoxy groups into the isocyanate, and the epoxy groups have good reactivity and can form bonds with the surfaces of various substrates, thereby improving the adhesion performance of the aluminum foil foam; the tackifier modified chain extender introduces high adhesion groups through chain extension modification, thereby improving the adhesion performance of the aluminum foil foam; the modified conductive filler has good system compatibility, can reinforce the molecular defects in the foam, and construct a conductive network, thereby improving the antistatic performance; the modified conductive filler can also absorb and scatter electromagnetic waves, dissipate the energy of electromagnetic waves, so that the foam can synergize with the aluminum foil, improve the shielding performance, and reduce the impact of external interference on electronic products.

[0038] 2. Polymerized rosin has good adhesion properties. The reactivity of polymerized rosin is improved by reacting oxalyl chloride with polymerized rosin, so that long-chain diols are successfully grafted onto the surface of polymerized rosin, and polymerized rosin is introduced into polymer molecules through chain extension reaction, thereby improving the adhesion and stability of aluminum foil foam; polymerized rosin has dielectric properties and wave absorbing properties, which can help improve antistatic and shielding properties; long-chain diamines have a long carbon chain structure, which can promote intermolecular cross-linking, form more hydrogen bonds and van der Waals forces, improve the durability and stability of aluminum foil foam, and optimize the pore structure of the foam, so that the aluminum foil foam can increase the absorption and reflection of electromagnetic waves through a uniform and delicate pore structure, thereby improving the shielding performance.

[0039] 3. A large number of electrons are distributed on the carbon atom orbits in conductive carbon black, carbon nanotubes and graphene oxide, forming a conjugated π electron system, so they have good conductivity and can effectively absorb electromagnetic waves. Through the oscillation of their own free electrons, they convert the energy of electromagnetic waves into heat energy, promote the attenuation and absorption of electromagnetic waves, and thus improve the antistatic and shielding properties; the aluminum foil foam is modified by boron silane and long-chain diamine to increase the active groups on the surface of the composite filler, thereby improving its system compatibility and reactivity, so that the modified conductive filler can better exert its antistatic and shielding properties. DETAILED DESCRIPTION

[0040] The present application discloses a highly adhesive aluminum foil foam and a processing technology thereof. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail below in conjunction with the embodiments:

[0041] Raw materials description: 1,4-butanediol diglycidyl ether (CAS No.: 2425-79-8), triethanolamine (CAS No.: 102-71-6), N,N-dimethylformamide (CAS No.: 68-12-2), diphenylmethane diisocyanate (CAS No.: 101-68-6), polymerized rosin (CAS No.: 8050-09-7), oxalyl chloride (CAS No.: 79-37-8), long-chain diol is 1,7-heptanediol (CAS No.: 629-30-1), triethylamine (CAS No.: 121-44-8), conductive carbon black model is Cabot VXC-72, carbon nanotubes and graphene oxide are purchased from Xianfeng Nano, boric acid (CAS No.: 10043-35-3), dichlorodicyclopentylsilane Alkane (CAS No.: 139147-73-2), long-chain diamine is 1,8-octanediamine (CAS No.: 373-44-4), polyether polyol (CAS No.: 9003-11-6), polyester polyol (CAS No.: 32472-85-8), bio-based polyol is purchased from Haoyi New Materials, model FX-9008, dibutyltin dilaurate (CAS: 77-58-7), blowing agent is 4,4'-oxybisbenzenesulfonyl hydrazide (CAS No.: 80-51-3), catalyst is N-methylmorpholine (CAS No.: 110-91-8) and triethylenediamine (CAS No.: 280-57-9), ethylene glycol (CAS No.: 107-21-1), propylenediamine (CAS No.: 78-90-0).

[0042] Example 1

[0043] Preparation of epoxy modified isocyanate

[0044] 2.32 kg of 1,4-butanediol diglycidyl ether was dispersed in 5 L of N,N-dimethylformamide to obtain a glycidyl ether solution, 1.74 kg of triethanolamine was dispersed in 5 L of N,N-dimethylformamide to obtain an alcoholamine solution, the alcoholamine solution was added to the glycidyl ether solution within 20 minutes, and then the reaction was kept at 25°C for 30 minutes to obtain an intermediate solution; 25.94 kg of diphenylmethane diisocyanate was dissolved in 50 L of N,N-dimethylformamide under nitrogen protection to obtain an isocyanate solution, the intermediate solution was added to the isocyanate solution at 60°C, the addition was completed within 1 hour, the reaction was kept at 25°C for 1 hour, and the solvent was removed from the solution after the reaction by rotary evaporation to obtain epoxy modified isocyanate.

[0045] Preparation of viscosity-enhancing modified chain extenders

[0046] 10 kg of polymerized rosin was dissolved in 20 L of tetrahydrofuran to obtain a rosin solution, 8.56 kg of oxalyl chloride was added to the rosin solution within 2 hours, the mixture was stirred at a speed of 200 rpm for reaction for 6 hours, and a preliminary modified product was obtained by rotary evaporation; 8.92 kg of long-chain diol and 6.83 kg of triethylamine were added to the preliminary modified product, the mixture was stirred at 200 rpm for reaction at 50° C. for 6 hours, and the mixture was cooled to below 30° C., filtered to obtain an organic phase, and the organic phase was washed three times with 0.1 mol / L of dilute hydrochloric acid and 0.1 mol / L of sodium carbonate aqueous solution, respectively, and the washed organic phase was dried in a vacuum oven at 50° C. to obtain a viscosity-enhancing modified chain extender.

[0047] Preparation of modified conductive fillers

[0048] The composite filler was washed three times with anhydrous ethanol, ball-milled for 6 hours and then dried in an oven at 80°C to obtain a pretreated composite filler, in which the mass ratio of conductive carbon black, carbon nanotubes and graphene oxide was 1:0.8:1.5; 1.21 kg of boric acid and 5.49 kg of dichlorodicyclopentylsilane were mixed and dispersed, reacted at 80°C under reduced pressure for 8 hours, and cooled to obtain boron-containing silane; 20 kg of the pretreated composite filler and the boron-containing silane prepared above were mixed and dispersed in 30 L of toluene, stirred at 200 rpm for 2 hours, then 2.5 L of deionized water was added, and the mixture was stirred at 200 rpm for 4 hours in a water bath at 80°C, and then 3.3 kg of long-chain diamine was added, and the mixture was stirred at 200 rpm for 4 hours in a water bath at 80°C, and the obtained product solution was filtered to obtain a filtrate, and the filtrate was washed with anhydrous ethanol, and the washed filtrate was dried in an oven at 80°C for 6 hours to obtain a modified conductive filler.

[0049] Preparation of high-adhesive aluminum foil foam

[0050] The composite polyol was dehydrated under reduced pressure at 110°C for 6 hours, cooled to below 40°C to obtain anhydrous composite polyol, dried and stored for later use, the mass ratio of polyether polyol, polyester polyol and bio-based polyol in the composite polyol was 1:1:2; 25 kg of anhydrous composite polyol was added to 15 kg of epoxy modified isocyanate under nitrogen protection within 2 hours to obtain a prepolymer mixture, 4 kg of viscosity-enhancing modified chain extender, 12 kg of modified conductive filler and 0.05 kg of dibutyltin dilaurate were mixed and added to the prepolymer mixture, stirred at a speed of 200 rpm, and kept warm for reaction at 80°C for 3 hours to obtain a prepolymer mixture. The prepolymer is prepared by mixing 1.5 kg of a blowing agent and 0.2 kg of a catalyst, wherein the mass ratio of N-methylmorpholine to triethylenediamine in the catalyst is 2:1, and the mixture is stirred at a speed of 200 rpm for 10 min to obtain a foaming mixture, and the foaming mixture is evenly coated on the surface of an aluminum foil to obtain a high-adhesive foam I, and a release paper I is covered on the high-adhesive foam I. The foaming mixture is turned over and evenly coated on the other side of the aluminum foil to obtain a high-adhesive foam II, and a release paper II is covered on the high-adhesive foam II to obtain a preliminary product, and the preliminary product is aged in an oven at 60°C for 8 h to obtain a high-adhesive aluminum foil foam.

[0051] Example 2

[0052] Preparation of epoxy-modified isocyanate

[0053] 1.95 kg of 1,4-butanediol diglycidyl ether was dispersed in 5 L of N,N-dimethylformamide to obtain a glycidyl ether solution, 1.47 kg of triethanolamine was dispersed in 5 L of N,N-dimethylformamide to obtain an alcoholamine solution, the alcoholamine solution was added to the glycidyl ether solution within 20 minutes, and then the reaction was kept at 25°C for 30 minutes to obtain an intermediate solution; 26.58 kg of diphenylmethane diisocyanate was dissolved in 50 L of N,N-dimethylformamide under nitrogen protection to obtain an isocyanate solution, the intermediate solution was added to the isocyanate solution at 60°C within 1 hour, the reaction was kept at this temperature for 1 hour, and the solvent was removed from the solution after the reaction by rotary evaporation to obtain epoxy modified isocyanate.

[0054] Preparation of viscosity-enhancing modified chain extenders

[0055] 10 kg of polymerized rosin was dissolved in 20 L of tetrahydrofuran to obtain a rosin solution, 8.56 kg of oxalyl chloride was added to the rosin solution within 2 hours, the mixture was stirred at a speed of 200 rpm for reaction for 6 hours, and a preliminary modified product was obtained by rotary evaporation; 8.92 kg of long-chain diol and 6.83 kg of triethylamine were added to the preliminary modified product, the mixture was stirred at 200 rpm for reaction at 50° C. for 6 hours, and the mixture was cooled to below 30° C., filtered to obtain an organic phase, and the organic phase was washed three times with 0.1 mol / L of dilute hydrochloric acid and 0.1 mol / L of sodium carbonate aqueous solution, respectively, and the washed organic phase was dried in a vacuum oven at 50° C. to obtain a viscosity-enhancing modified chain extender.

[0056] Preparation of modified conductive fillers

[0057] The composite filler was washed three times with anhydrous ethanol, ball-milled for 6 hours and then dried in an oven at 80°C to obtain a pretreated composite filler, in which the mass ratio of conductive carbon black, carbon nanotubes and graphene oxide was 1:0.8:1.5; 1.58 kg of boric acid and 5.26 kg of dichlorodicyclopentylsilane were mixed and dispersed, reacted at 80°C under reduced pressure for 8 hours, and cooled to obtain boron-containing silane; 20 kg of the pretreated composite filler and the boron-containing silane prepared above were mixed and dispersed in 30 L of toluene, stirred at 200 rpm for 2 hours, then 2.5 L of deionized water was added, stirred at 200 rpm in a water bath at 80°C for 4 hours, 3.16 kg of long-chain diamine was added, and the stirring reaction was continued at 200 rpm in a water bath at 80°C for 4 hours, and the obtained product solution was filtered to obtain a filtrate, the filtrate was washed with anhydrous ethanol, and the washed filtrate was dried in an oven at 80°C for 6 hours to obtain a modified conductive filler.

[0058] Preparation of high-adhesive aluminum foil foam

[0059] The composite polyol was dehydrated under reduced pressure at 110°C for 6 hours, cooled to below 40°C to obtain anhydrous composite polyol, dried and stored for later use, the mass ratio of polyether polyol, polyester polyol and bio-based polyol in the composite polyol was 1:1:2; 35 kg of anhydrous composite polyol was added to 25 kg of epoxy modified isocyanate under nitrogen protection within 2 hours to obtain a prepolymer mixture, 6 kg of viscosity-enhancing modified chain extender, 16 kg of modified conductive filler and 0.15 kg of dibutyltin dilaurate were mixed and added to the prepolymer mixture, stirred at a speed of 200 rpm, and kept warm for reaction at 80°C for 3 hours to obtain a prepolymer mixture. The prepolymer is prepared by mixing 2.5 kg of foaming agent and 0.6 kg of catalyst into the prepolymer, wherein the mass ratio of N-methylmorpholine to triethylenediamine in the catalyst is 2:1, and the mixture is stirred at a speed of 200 rpm for 10 min to obtain a foaming mixture, and the foaming mixture is evenly coated on the surface of an aluminum foil to obtain a high-adhesive foam I, and a release paper I is covered on the high-adhesive foam I. The foaming mixture is turned over and evenly coated on the other side of the aluminum foil to obtain a high-adhesive foam II, and a release paper II is covered on the high-adhesive foam II to obtain a preliminary product, and the preliminary product is aged in an oven at 60°C for 8 h to obtain a high-adhesive aluminum foil foam.

[0060] Example 3

[0061] Preparation of epoxy modified isocyanate

[0062] 2.12 kg of 1,4-butanediol diglycidyl ether was dispersed in 5 L of N,N-dimethylformamide to obtain a glycidyl ether solution, 1.59 kg of triethanolamine was dispersed in 5 L of N,N-dimethylformamide to obtain an alcoholamine solution, the alcoholamine solution was added to the glycidyl ether solution within 20 minutes, and then the reaction was kept at 25°C for 30 minutes to obtain an intermediate solution; 26.29 kg of diphenylmethane diisocyanate was dissolved in 50 L of N,N-dimethylformamide under nitrogen protection to obtain an isocyanate solution, the intermediate solution was added to the isocyanate solution at 60°C, the addition was completed within 1 hour, the reaction was kept at 25°C for 1 hour, and the solvent was removed from the solution after the reaction by rotary evaporation to obtain epoxy modified isocyanate.

[0063] Preparation of viscosity-enhancing modified chain extenders

[0064] 10 kg of polymerized rosin was dissolved in 20 L of tetrahydrofuran to obtain a rosin solution, 8.56 kg of oxalyl chloride was added to the rosin solution within 2 hours, the mixture was stirred at a speed of 200 rpm for reaction for 6 hours, and a preliminary modified product was obtained by rotary evaporation; 8.92 kg of long-chain diol and 6.83 kg of triethylamine were added to the preliminary modified product, the mixture was stirred at 200 rpm for reaction at 50° C. for 6 hours, and the mixture was cooled to below 30° C., filtered to obtain an organic phase, and the organic phase was washed three times with 0.1 mol / L of dilute hydrochloric acid and 0.1 mol / L of sodium carbonate aqueous solution, respectively, and the washed organic phase was dried in a vacuum oven at 50° C. to obtain a viscosity-enhancing modified chain extender.

[0065] Preparation of modified conductive fillers

[0066] The composite filler was washed three times with anhydrous ethanol, ball-milled for 6 hours and then dried in an oven at 80°C to obtain a pretreated composite filler, in which the mass ratio of conductive carbon black, carbon nanotubes and graphene oxide was 1:0.8:1.5; 1.4 kg of boric acid and 5.38 kg of dichlorodicyclopentylsilane were mixed and dispersed, reacted at 80°C under reduced pressure for 8 hours, and cooled to obtain boron-containing silane; 20 kg of the pretreated composite filler and the boron-containing silane prepared above were mixed and dispersed in 30 L of toluene, stirred at 200 rpm for 2 hours, then 2.5 L of deionized water was added, and the mixture was stirred at 200 rpm in a water bath at 80°C for 4 hours, and then 3.22 kg of long-chain diamine was added, and the mixture was stirred at 200 rpm in a water bath at 80°C for 4 hours, and the obtained product solution was filtered to obtain a filtrate, and the filtrate was washed with anhydrous ethanol, and the washed filtrate was dried in an oven at 80°C for 6 hours to obtain a modified conductive filler.

[0067] Preparation of high-adhesive aluminum foil foam

[0068] The composite polyol was dehydrated at 110°C under reduced pressure for 6 hours, cooled to below 40°C to obtain anhydrous composite polyol, dried and stored for later use, the mass ratio of polyether polyol, polyester polyol and bio-based polyol in the composite polyol was 1:1:2; 30 kg of anhydrous composite polyol was added to 20 kg of epoxy modified isocyanate under nitrogen protection within 2 hours to obtain a prepolymer mixture, 5 kg of viscosity-enhancing modified chain extender, 14 kg of modified conductive filler and 0.1 kg of dibutyltin dilaurate were mixed and added to the prepolymer mixture, stirred at a speed of 200 rpm, and kept warm for reaction at 80°C for 3 hours to obtain prepolymer, 2kg of blowing agent and 0.4kg of catalyst are dispersed in the prepolymer, the mass ratio of N-methylmorpholine and triethylenediamine in the catalyst is 2:1, and stirred at a speed of 200rpm for 10min to obtain a foaming mixture, and the foaming mixture is evenly coated on the surface of aluminum foil to obtain high-adhesion foam I, and release paper I is covered on the high-adhesion foam I, turned over, and the foaming mixture is evenly coated on the other side of the aluminum foil to obtain high-adhesion foam II, and release paper II is covered on the high-adhesion foam II to obtain a preliminary product, and the preliminary product is aged in an oven at 60℃ for 8h to obtain a high-adhesion aluminum foil foam.

[0069] Example 4

[0070] Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, the complex polyol is replaced by polyether polyol and bio-based polyol.

[0071] Example 5

[0072] Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, the complex polyol is replaced by polyester polyol.

[0073] Example 6

[0074] Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, the amount of 1,4-butanediol diglycidyl ether is 2.55 kg, the amount of triethanolamine is 1.91 kg, and the amount of diphenylmethane diisocyanate is 25.54 kg.

[0075] Example 7

[0076] Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that in Example 7, the amount of 1,4-butanediol diglycidyl ether is 1.79 kg, the amount of triethanolamine is 1.34 kg, and the amount of diphenylmethane diisocyanate is 26.87 kg.

[0077] Example 8

[0078] Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that in Example 8, the long-chain diol is replaced by ethylene glycol when preparing the viscosity-enhancing modified chain extender.

[0079] Example 9

[0080] Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that in Example 9, the amount of boric acid used is 0.86 kg, the amount of dichlorodicyclopentylsilane used is 5.71 kg, and the amount of long-chain diamine used is 3.43 kg.

[0081] Example 10

[0082] Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that in Example 10, the amount of boric acid used is 1.79 kg, the amount of dichlorodicyclopentylsilane used is 5.13 kg, and the amount of long-chain diamine used is 3.08 kg.

[0083] Embodiment 11

[0084] Example 11 is based on Example 3. The only difference between Example 11 and Example 3 is that in Example 11, the composite filler used in preparing the modified conductive filler is replaced with conductive carbon black and carbon nanotubes.

[0085] Example 12

[0086] Example 12 is based on Example 3. The only difference between Example 12 and Example 3 is that in Example 12, the composite filler used in preparing the modified conductive filler is replaced with graphene oxide.

[0087] Example 13

[0088] Example 13 is based on Example 3. The only difference between Example 13 and Example 3 is that in Example 13, the boron-containing silane is replaced by dichlorodicyclopentylsilane when preparing the modified conductive filler.

[0089] Embodiment 14

[0090] Example 14 is based on Example 3. The only difference between Example 14 and Example 3 is that in Example 14, the long-chain diamine is replaced by propylene diamine when preparing the modified conductive filler.

[0091] Embodiment 15

[0092] Example 15 is based on Example 3, and the only difference between Example 15 and Example 3 is that in Example 15, the foaming agent is replaced by deionized water.

[0093] Example 16

[0094] Example 16 is based on Example 3, and the only difference between Example 16 and Example 3 is that in Example 16, the catalyst is replaced by N-methylmorpholine.

[0095] Comparative Example 1

[0096] Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the epoxy-modified isocyanate is replaced by diphenylmethane diisocyanate.

[0097] Comparative Example 2

[0098] Comparative Example 2 is based on Example 3, and the only difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, the viscosity-enhancing modified chain extender is replaced by a long-chain diol.

[0099] Comparative Example 3

[0100] Comparative Example 3 is based on Example 3, and the only difference between Comparative Example 3 and Example 3 is that in Comparative Example 3, the modified conductive filler is replaced by conductive carbon black.

[0101] Performance testing

[0102] (1) GB / T2792-2014 Test method for peel strength of adhesive tape was selected as the standard, and the 180° peel strength of aluminum foil foam was tested using a desktop tensile testing machine. Three samples were prepared for each test specimen, and the average value was taken after measurement. The results were recorded in Table 1.

[0103] (2) Select "ASTM-D257 Test Method for DC Resistance or Conductivity of Insulating Materials" as the standard, and use a surface resistance meter to test the surface impedance of aluminum foil foam. Each sample is tested three times, and the average value is taken after measurement. The results are recorded in Table 1.

[0104] (3) Select "GB / T42718-2023 General Technical Requirements for Electromagnetic Shielding Effectiveness of Wrapped Foam Pads" as the standard, place the aluminum foil foam in the test room, conduct shielding performance tests, and record the maximum absorption value. Each sample is tested three times, and the average value is taken after measurement. The results are recorded in Table 1.

[0105] Table 1 Test results of adhesion, antistatic and shielding properties of high adhesion aluminum foil foam

[0106] Test results Peel force (N / 25mm) Surface impedance(Ω) Maximum absorption value (dB) Example 1 22.3 <![CDATA[1.8*10 8 ]]> -36.8 Example 2 22.9 <![CDATA[1.8*10 8 ]]> -37.2 Example 3 23.6 <![CDATA[1.9*10 8 ]]> -37.6 Example 4 21.6 <![CDATA[1.8*10 8 ]]> -35.2 Example 5 21.1 <![CDATA[1.7*10 8 ]]> -34.7 Example 6 21.8 <![CDATA[1.6*10 8 ]]> -34.9 Example 7 22.2 <![CDATA[1.7*10 8 ]]> -35.3 Example 8 20.7 <![CDATA[1.5*10 8 ]]> -32.1 Example 9 21.2 <![CDATA[1.6*10 8 ]]> -33.6 Example 10 20.6 <![CDATA[1.4*10 8 ]]> -32.5 Embodiment 11 22.4 <![CDATA[1.5*10 8 ]]> -32.9 Example 12 21.9 <![CDATA[1.3*10 8 ]]> -30.1 Example 13 20.4 <![CDATA[1.6*10 8 ]]> -32.7 Embodiment 14 20.8 <![CDATA[0.9*10 8 ]]> -28.4 Embodiment 15 19.2 <![CDATA[0.8*10 8 ]]> -26.5 Example 16 19.6 <![CDATA[0.9*10 8 ]]> -27.8 Comparative Example 1 16.8 <![CDATA[1.2*10 8 ]]> -29.3 Comparative Example 2 15.3 <![CDATA[0.5*10 8 ]]> -20.7 Comparative Example 3 19.6 <![CDATA[0.2*10 8 ]]> -15.7

[0107] As shown in Table 1, the peeling force of Examples 1-3 is greater than 22.3N / 25mm, and the surface impedance is greater than 1.8*10 8 Ω, and the maximum absorption value is greater than -36.8dB, which shows that the aluminum foil foam prepared in the present application has high adhesion, good antistatic performance and shielding performance.

[0108] As can be seen from Table 1, the only difference between Examples 4 and 5 and Example 3 is that in Example 4, the complex polyol is replaced by polyether polyol and bio-based polyol, and in Example 5, the complex polyol is replaced by polyester polyol. Compared with Example 3, the adhesion performance, antistatic performance and shielding performance of Examples 4 and 5 are all reduced; this is because the types of polyols in the complex polyol are reduced, the types of active groups on the polyol are reduced, the reactivity and the role of forming chemical bonds are reduced, and thus the adhesion performance, antistatic performance and shielding performance are all reduced.

[0109] As can be seen from Table 1, the only difference between Examples 6 and 7 and Example 3 is that the mass ratio of 1,4-butanediol diglycidyl ether, triethanolamine and diphenylmethane diisocyanate in Example 6 is 1:0.75:10, and the mass ratio of 1,4-butanediol diglycidyl ether, triethanolamine and diphenylmethane diisocyanate in Example 7 is 1:0.75:15. Compared with Example 3, the adhesion performance, antistatic performance and shielding performance of Examples 6 and 7 are all reduced; this is because the mass ratio of 1,4-butanediol diglycidyl ether, triethanolamine and diphenylmethane diisocyanate is not within the limited range, and the reactivity of the epoxy-modified isocyanate obtained within the optimal ratio range is reduced, which affects the cross-linking structure of the polymer network and the chemical bonding between molecules, and the stability is reduced, thereby reducing the adhesion performance, antistatic performance and shielding performance.

[0110] As can be seen from Table 1, the only difference between Example 8 and Example 3 is that in Example 8, the long-chain diol is replaced by ethylene glycol when preparing the viscosity-enhancing modified chain extender. Compared with Example 3, the adhesion performance, antistatic performance and shielding performance of Example 8 are all reduced; this is because the long-chain diol is replaced by ethylene glycol, the reactivity of the viscosity-enhancing modified chain extender is reduced due to steric hindrance, and the short carbon chain leads to reduced crosslinking and chemical bonding between molecules, thereby reducing the adhesion performance, antistatic performance and shielding performance.

[0111] As can be seen from Table 1, the only difference between Examples 9 and 10 and Example 3 is that the mass ratio of boric acid, dichlorodicyclopentylsilane and long-chain diamine in Example 9 is 0.15:1:0.6, and the mass ratio of boric acid, dichlorodicyclopentylsilane and long-chain diamine in Example 10 is 0.35:1:0.6. Compared with Example 3, the adhesion performance, antistatic performance and shielding performance of Examples 9 and 10 are all reduced; this is because the mass ratio of boric acid, dichlorodicyclopentylsilane and long-chain diamine is not within the specified range, the modification effect of the modifier obtained by destroying the optimal ratio is reduced, the reactivity and compatibility of the modified conductive filler are deteriorated, and the gain effect is affected, so that the adhesion performance, antistatic performance and shielding performance are all reduced.

[0112] As can be seen from Table 1, the only difference between Examples 11, 12, 13, and 14 and Example 3 is that in Example 11, the composite filler used in preparing the modified conductive filler is replaced with conductive carbon black and carbon nanotubes, in Example 12, the composite filler used in preparing the modified conductive filler is replaced with graphene oxide, in Example 13, the boron-containing silane is replaced with dichlorodicyclopentylsilane when preparing the modified conductive filler, and in Example 14, the long-chain diamine is replaced with propylene diamine when preparing the modified conductive filler. Compared with Example 3, Examples 11, 12, 13, and 14 have reduced adhesion, antistatic, and shielding properties; this is because the types of composite fillers are reduced, the synergistic effect between the fillers is weakened, and thus the performance is reduced; not adding boron will affect the bonding force between the foam and the substrate; replacing the long-chain diamine with propylene diamine, the short carbon chain will reduce cross-linking and chemical bonding, and thus the adhesion, antistatic, and shielding properties are reduced.

[0113] As can be seen from Table 1, the only difference between Examples 15 and 16 and Example 3 is that the foaming agent in Example 15 is replaced by deionized water, and the catalyst in Example 16 is replaced by N-methylmorpholine. Compared with Example 3, the adhesion performance, antistatic performance and shielding performance of Examples 15 and 16 are reduced; this is because the replacement of the foaming agent and the catalyst will affect the composite synergistic effect of the two, the pore structure of the foam will deteriorate, and the uniformity and fineness will decrease, thereby reducing the adhesion performance, antistatic performance and shielding performance.

[0114] As can be seen from Table 1, the only difference between Comparative Example 1 and Example 3 is that: in Comparative Example 1, the epoxy-modified isocyanate is replaced by diphenylmethane diisocyanate. Compared with Example 3, the adhesion performance, antistatic performance and shielding performance of Comparative Example 1 are significantly reduced; this is because the epoxy-modified isocyanate is replaced by diphenylmethane diisocyanate, lacks the introduction of epoxy groups, the reaction activity is reduced, the cross-linking structure is reduced, and the overall stability of the foam system is affected, so that the adhesion performance, antistatic performance and shielding performance are significantly reduced.

[0115] As can be seen from Table 1, the only difference between Comparative Example 2 and Example 3 is that the viscosity-enhancing modified chain extender is replaced by a long-chain diol in Comparative Example 2. Compared with Example 3, the adhesion performance, antistatic performance and shielding performance of Comparative Example 2 are significantly reduced; this is because the viscosity-enhancing modified chain extender is replaced by a long-chain diol, and the long-chain diol lacks the introduction of polymerized rosin, which affects the adhesion performance and the stability of the system, thereby significantly reducing the adhesion performance, antistatic performance and shielding performance.

[0116] As can be seen from Table 1, the only difference between Comparative Example 3 and Example 3 is that the modified conductive filler in Comparative Example 3 is replaced by conductive carbon black. Compared with Example 3, the adhesion performance, antistatic performance and shielding performance of Comparative Example 3 are significantly reduced; this is because the modified conductive filler is replaced by conductive carbon black, lacks the compounding effect of multiple fillers and the modification treatment of the modifier, the system compatibility of the conductive carbon black is reduced, and the effect of improving the adhesion performance, antistatic performance and shielding performance is reduced, so that the adhesion performance, antistatic performance and shielding performance are significantly reduced.

[0117] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A high-adhesion aluminum foil foam, characterized in that: The high-adhesive aluminum foil foam comprises release paper I, high-adhesive foam I, aluminum foil, high-adhesive foam II and release paper II arranged in sequence, and the high-adhesive foam comprises the following components in parts by mass: 25-35 parts of compound polyol Epoxy modified isocyanate 15-25 parts 4-6 parts of viscosity-enhancing modified chain extender Modified conductive filler 12-16 parts Dibutyltin dilaurate 0.05-0.15 parts Foaming agent 1.5-2.5 parts Catalyst 0.2-0.6 parts; The raw materials for preparing the epoxy-modified isocyanate include 1,4-butanediol diglycidyl ether, triethanolamine and diphenylmethane diisocyanate; The raw materials for preparing the viscosity-increasing modified chain extender include polymerized rosin, oxalyl chloride and long-chain diol; The long-chain diol is 1,7-heptanediol; The raw materials for preparing the modified conductive filler include a composite filler and a modifier, the composite filler includes conductive carbon black, carbon nanotubes and graphene oxide, and the raw materials for preparing the modifier include boron-containing silane and long-chain diamine; The long-chain diamine is 1,8-octanediamine; The catalyst includes N-methylmorpholine and triethylenediamine.

2. The high-adhesion aluminum foil foam according to claim 1, characterized in that: The complex polyols include polyether polyols, polyester polyols and bio-based polyols.

3. The high-adhesion aluminum foil foam according to claim 1, characterized in that: The mass ratio of the 1,4-butanediol diglycidyl ether, triethanolamine and diphenylmethane diisocyanate is 1:0.75:(11.2-13.6).

4. The high-adhesion aluminum foil foam according to claim 1, characterized in that: The raw materials for preparing the boron-containing silane include boric acid and dichlorodicyclopentylsilane.

5. The high-adhesion aluminum foil foam according to claim 4, characterized in that: The mass ratio of the boric acid, dichlorodicyclopentylsilane and long-chain diamine is (0.22-0.3):1:0.

6.

6. The high-adhesion aluminum foil foam according to claim 1, characterized in that: The foaming agent includes 4,4'-oxybisbenzenesulfonyl hydrazide.

7. A processing technology for the high-adhesion aluminum foil foam as claimed in claim 1, characterized in that: The steps include: The composite polyol is heated and decompressed to dehydrate to obtain an anhydrous composite polyol, which is dried and stored for later use; under the protection of a neutral gas, the anhydrous composite polyol is added to an epoxy-modified isocyanate to obtain a prepolymer mixture, a tackifier-modified chain extender, a modified conductive filler and dibutyltin dilaurate are mixed and added to the prepolymer mixture, heated and stirred to react to obtain a prepolymer, a blowing agent and a catalyst are dispersed in the prepolymer, stirred to obtain a foaming mixture, the foaming mixture is uniformly coated on the surface of an aluminum foil to obtain a high-adhesion foam I, a release paper I is covered on the high-adhesion foam I, the surface is turned over, and the foaming mixture is uniformly coated on the other side of the aluminum foil to obtain a high-adhesion foam II, a release paper II is covered on the high-adhesion foam II to obtain a preliminary product, and the preliminary product is matured to obtain a high-adhesion aluminum foil foam.

Citation Information

Patent Citations

  • Silane modified polyethylene material and preparation method thereof

    CN106317574A

  • Adhesive with epoxy resin and method for preparing adhesive

    CN109439267A